2004
DOI: 10.1562/2004-04-06-ra-136.1
|View full text |Cite
|
Sign up to set email alerts
|

Photodecomposition of Pigment Yellow 74, a Pigment Used in Tattoo Inks¶

Abstract: Tattooing has become a popular recreational practice among younger adults over the past decade. Although some of the pigments used in tattooing have been described, very little is known concerning the toxicology, phototoxicology or photochemistry of these pigments. Seven yellow tattoo inks were obtained from commercial sources and their pigments extracted, identified and quantitatively analyzed. The monoazo compound Pigment Yellow 74 (PY74; CI 11741) was found to be the major pigment in several of the tattoo i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…Five percent of the participants noticed a fading of the initial tattoo color (table 2). In case azo pigments are decomposed by any kind of radiation, hazardous products appear in skin, which has already been proven in vitro [30,31]. Besides coloring the skin, tattoo colorants are transported inside the body like medical drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five percent of the participants noticed a fading of the initial tattoo color (table 2). In case azo pigments are decomposed by any kind of radiation, hazardous products appear in skin, which has already been proven in vitro [30,31]. Besides coloring the skin, tattoo colorants are transported inside the body like medical drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Such pigments can strongly absorb the ultraviolet part of solar radiation and are able to generate reactive oxygen species that might be responsible for those adverse skin reactions. At the same time, azo pigments can be decomposed to the corresponding hazardous aromatic amines [30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, some focus has shifted from identifying the organic pigments themselves to the products created by photodecomposition through laser or UV/sunlight exposure. Using a combination of HPLC, MS, UV/visible spectroscopy and proton nuclear magnetic resonance spectroscopy ( 1 H-NMR), specific organic pigments (monoazo Pigment Yellow 74 22 and naphthol AS Pigment Red 22 23 ) were found to be susceptible to cleavage by natural and simulated solar light and long-wave ultraviolet radiation into potentially toxic or carcinogenic aromatic amines. A recent survey 24 published in September 2006 revealed that almost 25% of people in the United States had one or more tattoos, with 17% of them having considered undergoing treatment to remove their tattoos.…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H-NMR spectra of the studied compounds showed signal in the region of δ= 13.72-14.42 ppm assignable to hydrazone proton (-CH= N-NH-). [26][27][28] Signal at δ= 5.27 29) ppm, which is characteristic for the CH protons of CH-azo form, was not detected. Also, IR spectra did not reveal broad signal at 3434 cm −1 , which is characteristic for OH of azo-enol form.…”
Section: Resultsmentioning
confidence: 96%